Estimates of regional infectivity of COVID-19 in the United Kingdom following imposition of social distancing measures. (31st May 2021) - Challen, Robert; Tsaneva-Atanasova, Krasimira; Pitt, Martin; Edwards, Tom; Gompels, Luke; Lacasa, Lucas; Brooks-Pollock, Ellen; Danon, Leon
Abstract : The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) reproduction number has become an essential parameter for monitoring disease transmission across settings and guiding interventions. The UK published weekly estimates of the reproduction number in the UK starting in May 2020 which are formed from multiple independent estimates. In this paper, we describe methods used to estimate the time-varying SARS-CoV-2 reproduction number for the UK. We used multiple data sources and estimated a serial interval distribution from published studies. We describe regional variability and how estimates evolved during the early phases of the outbreak, until the relaxing of social distancing measures began to be introduced in early July. Our analysis is able to guide localized control and provides a longitudinal example of applying these methods over long timescales. This article is part of the theme issue 'Modelling that shaped the early COVID-19 pandemic response in the UK'.